DETERMINANTS OF NON-MUSLIM CONSUMERS’ PURCHASE BEHAVIOR TOWARD HALAL PACKAGED FOOD - Untari, Asih; Safira, Anya (ASEAN Marketing Journal, 2021)
Manuscript type: Research article Research Aims: The objective of this research is to determine factors affecting the purchase behavior of non-Muslim consumers toward halal packaged food. Design/methodology/approach: Data was collected from self-adminstrated questionnaire from non-Muslim consumers who have purchased halal packaged food. Structural Equation Modelling (SEM) using SmartPLS was used to analyze the effect of attitude, subjective norm, perceived behavioral control, halal logo and halal marketing on purchase intention and purchase behavior. Research Findings: Only subjective norm, halal logo and halal marketing affect purchase intention, which later affects purchase behavior. Meanwhile perceived behavioral control was found to directly affect purchase behavior. Theoretical Contribution/Originality: This research contributes further to the body of knowledge regarding the Theory of Planned Behavior, and has investigated that the theory can also be applied in the context of non-Muslim consumers’ purchase intention toward halal packaged food. Practitioner/Policy Implication: From the findings, practitioners in the field of halal packaged food can formulate strategies regarding halal marketing and subjective norm in order to stimulate consumers’ purchase intention. Research limitation/Implications: There are several research limitations regarding the screening question and a few indicators used which in future research is suggested to be a better reflection of the research variales and objectives.